Odpowiedzi

2009-11-05T16:40:57+01:00
D) -2a(x-1) + (4a - 2)(x+5)=
= -2ax + 2a + 4ax + 20a - 2x - 10 =
= 2ax + 22a - 2x - 10

e) (2a-b)(3a+2b)-4a(5b-2a)+(a-b)(2a-4b)=
= 6a² + 4ab - 3ab - 2b² - 20ab + 8a² + 2a² - 4ab - 2ab + 4b² =
= 16a² + 2b² - 27ab

f) -[-(-x+y)(y-x)-(2x+y)(2y-x)]+4xy=
= - [ - ( -xy + x² + y² - xy) - (4xy - 2x² + 2y² - xy) ] + 4xy =
= - ( 2xy - x² - y² - 3xy + 2x² +2y²) + 4xy =
= - ( x² + y² - xy) + 4xy =
= -x² - y² + xy + 4xy =
= -x² - y² + 5xy
Najlepsza Odpowiedź!
2009-11-05T16:45:10+01:00
D) -2a(x-1)+(4a-2)(x+5)=-2ax+2a+4ax+20a-2x-10=2ax+22a-2x-10
e)(2a-b)(3a+2b)-4a(5b-2a)+(a-b)(2a-4b)=6a²+4ab-3ab-2ab-20ba+8a²+2a²-4ab-2ab+4b²=16a²+4b²-9ab
f)-[-(x+y)(y-x)-(2x+y)(2y-x)]+4xy=-[-xy+x²-y²+xy-4xy+2x²-2y²+xy]+4xy=-3x²+3y²+7xy